Mobility aware and reliable multipath routing protocol for MANETs. (5th October 2022) - Sarkar, Sajal
In this paper, a mobility aware and reliable multipath routing protocol (MR-AOMDV) is proposed for mobile ad hoc networks (MANETs). The proposed MR-AOMDV establishes multiple paths from source to destination considering mobility and reliability of nodes together as routing metrics for mobility aware and reliable data exchanges. In path discovery phase, the routing paths are constructed by comparing the values of mobility and reliability with the thresholds defined by a trust management module. In path maintenance phase, the constructed paths are adaptively modified by replacing, eliminating or including a node to make it more mobility aware and reliable paths. The constructed paths are stable and reliable, which are demonstrated by simulation results. MR-AOMDV improves performance and ensures security of data by exchanging it through the malicious-node free paths from source to destination. The simulation results of MR-AOMDV and existing protocols are presented for comparison and analysis, in which it was shown that MR-AOMDV achieves promising performance gain compared to the existing protocols in terms of throughput, energy consumption, packet delivery ratio, routing overhead, and end-to-end delay in different scenarios of a MANET.